Pemodelan Dan Simulasi Transformator Pada Kondisi Open-Circuit Pada Salah Satu Fasanya - Silitonga, Horin Relevando; Anto, Budhi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The transformer is widely used for increasing and decreasing the voltage of the power system. Loading on the transformer impact the reliability of the transformer. Sometimes an interruption in the transformer that causes malfunction of transformers, which are open-circuit. This paper describes how the condition occurs in the transformer during an open-circuit. Modeling conducted to observe the characteristics of the transformer. Modeling done by modeling the iron core construction purposes 400kVA step-down transformer 20KV / 400V by using software MATLAB / Simulink R2015A. The results of this paper to show the characteristics of the transformer which indicates that there is an unbalance between voltage and current on the primary side and secondary on the transformer.Keywords : three phase transformer, open-circuit, fault, modeling, MATLAB/Simulink